2012
DOI: 10.2139/ssrn.2030726
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Global Liquidity on Commodity and Food Prices

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…This is specifically important in light of the dependence on primary commodities and food markets and their influence on growth in developing countries (see Belke & Schnabl, ). Empirical evidence suggests that in the last three decades, there has been a significant change in the way the global commodity and primary markets operate which has also affected the market fundamentals (e.g., Belke, Bordon, & Volz, )—which is captured by the GMM estimator.…”
Section: Resultsmentioning
confidence: 99%
“…This is specifically important in light of the dependence on primary commodities and food markets and their influence on growth in developing countries (see Belke & Schnabl, ). Empirical evidence suggests that in the last three decades, there has been a significant change in the way the global commodity and primary markets operate which has also affected the market fundamentals (e.g., Belke, Bordon, & Volz, )—which is captured by the GMM estimator.…”
Section: Resultsmentioning
confidence: 99%
“…Comparing the findings to the previous literature, it can be concluded that the general implications which have been empirically shown for various commodity and food prices (see, for instance, Belke et al ., ) also hold for the price of gold in the long run. Global excess liquidity, measured as the difference between global money and global output, significantly enters a long‐run equilibrium relationship with the real price of gold.…”
Section: Empirical Analysismentioning
confidence: 89%
“…However, turning to the more general field of commodities and asset prices, there are a number of papers investigating the relationships between money, output, consumer prices, commodity prices, stocks, and housing prices by means of multivariate cointegration analysis (CVAR) for a number of countries, aggregating the respective time series to obtain “global” measures for the country sample (e.g., Giese and Tuxen, , Belke et al ., ,b and Belke et al ., ). The general conclusion is that global money growth has in many cases contributed to price increases in the respective variables.…”
Section: Literature Reviewmentioning
confidence: 97%
See 2 more Smart Citations